Implementasi Leadership, Quality Work, dan Team Work Terhadap Kinerja Crew Lion Air - Eneng Wiliana; Siti Aisyah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to find out how the influence of leadership, quality work, and team work on the performance of Lion Air. This study used a quantitative approach. The population was 2.572 employees and the sample in this study was 100 employees at Lion Air by using Slovin formula. Data were collected through initial observations, questionnaires, and interview. The analysis technique uses multiple linear regression. The results showed that partially, the Leadership variable (X1) has a significant effect on Crew Performance (Y). This is indicated by t count > t table i.e. t count 2.386 > t table 1.984 with a significant level of 0.000 or less than 0.05. The Quality Work variable (X2) has a significant effect on Crew Performance (Y). This is indicated by t count > t table, namely t count 7.075 > t table 1.984 with a significant level of 0.000 or less than 0.05. The Team Work variable (X3) has a significant effect on Crew Performance (Y). This is indicated by t count > t table i.e. t count 5.500 > t table 1.984 with a significant level of 0.000 or less than 0.05. Simultaneously the variables Leadership (X1), Quality Work (X2), and Teamwork (X3) have a positive effect on Crew Performance (Y), namely F calculate > F table of 92.035 > 2.70. With the value of the multiple regression equation Y = 6.046 + 0.618 X1 + 0.236 X2 + 0.003X3. The results of the multiple correlation test between X1, X2, and X3 against Y obtained a correlation value (R) of 0.813 or 81.3%.